Norma Pertumbuhan Untuk Indonesia - T. Jacob T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
This article argues for the existence of racial or even subracial differences in growth rhythm, so that more than one growth standard has to be used for world populations.For Indonesia, the application of a certain percentile of the Harvard—Iowa standard as norm is not recommended because of the different timing of growth spurts and allometry. Before an propriate norm is established, it is suggested to utilize the Chiang Mai growth diagram which in the author's opinion fits the growth pattern in Indonesian children very well.Key Words. growth norm - body height - allometry growth spurt - auxology